Islamic finance litigation: problems within the Malaysian Civil Courts structure - Hizri Hasshan (Penerbit Universiti Kebangsaan Malaysia, 2016)
Islamic finance litigation is an area of practice which involves application of Shari‘ah law, civil legislations, rules of court and the common law. In the year of 2003, the Malaysian judiciary has taken an administrative step to establish a Muamalat Division at the Kuala Lumpur High Court for adjudication of Islamic financial cases. However, this research observes that the jurisdiction of the said Division is limited to certain types of legal proceedings and confined to certain territorial limit. Moreover, the Rules of Court 2012 contain no provisions to regulate Islamic finance litigation proceedings. Hence, this research will attempt to identify and critically analyse the problems and flaws with the Malaysian judicial framework in relation to Islamic finance cases.